2013
DOI: 10.1177/0300060513483417
|View full text |Cite
|
Sign up to set email alerts
|

Impact of type 1 diabetes mellitus on academic performance

Abstract: Objective: To examine the effect of type 1 diabetes on academic performance. Methods: Ethnically Saudi students with type 1 diabetes, and age, sex, ethnicity and socioeconomic status-matched nondiabetic control students were recruited from eight schools. Overall academic grades were recorded, based on the scores obtained in written examinations in English, mathematics, physics, chemistry, biology and humanities. Results: Students with type 1 diabetes (n ¼ 36) obtained significantly lower academic grades compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
2
11
0
1
Order By: Relevance
“…Although this is justified through the impact of these tests on adult life chances, this criteria excluded studies which have otherwise suitable study designs for exploring the association between diabetes and educational outcomes, such as Cooper et al 7. This restriction also excluded studies which lack national standardised testing or administrative data records, either because they considered cohorts prior to such testing regimes33 or were studies from countries without such testing regimes 34 35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is justified through the impact of these tests on adult life chances, this criteria excluded studies which have otherwise suitable study designs for exploring the association between diabetes and educational outcomes, such as Cooper et al 7. This restriction also excluded studies which lack national standardised testing or administrative data records, either because they considered cohorts prior to such testing regimes33 or were studies from countries without such testing regimes 34 35…”
Section: Discussionmentioning
confidence: 99%
“…However, other diagnosed (or undiagnosed) comorbidities within this cohort may affect educational attainment and should be taken into consideration. For example, Meo et al 35 exclude cases with a range of health conditions (reported tobacco use, gross anaemia, tuberculosis, rheumatic fever, rheumatoid arthritis, vision problems, hearing problems or behavioural problems, use of any medication or hospital admissions other than for diabetes mellitus) to reduce the effect of other comorbidities within the cohort. An alternative to matching with healthy controls is to compare attainment for children with T1DM with children with other health conditions, in order to evaluate the mechanisms through which diabetes affects attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Although students with T1DM had a significantly lower academic performance than their non-diabetic classmates [11] (Table 1), they and their unaffected siblings had no significant differences on measures of cognitive performance, academic achievement, or speech ability [12] (Table 1).…”
Section: Cognitive Changes In T1dm Patientsmentioning
confidence: 98%
“…Such conditions, even in the absence of obesity, have been linked to cognitive dysfunction and decreases in brain volume (10)(11)(12)(13). Little research has been done exploring the effects of obesity on brain structure and cognition in obese, but otherwise healthy, individuals.…”
mentioning
confidence: 99%